Peran Pojoksatu.id dalam Menyebarkan Informasi (Studi Kasus: Media Sosial Tiktok, Instagram dan Facebook) - Asmilawati Putri; Firman Maulana Akhsan; Moch Rizki Fathir; Rahma Tiara Putri; Ulan Damayanti; Zahra Salsabiila; Rofi’ah Siddiq (KOLONI, 2024)
The role of mass media in influencing society is crucial, especially in Indonesia, where the majority of the population relies on mass media as their primary source of information. With the rapid development of technology and ease of access to information, social media has become the dominant platform for accessing the latest information. In this digital era, social media has evolved into the main stage for disseminating information to the public. This research examines the role of Pojoksatu.id in disseminating information through three main social media platforms: TikTok, Instagram, and Facebook. Using a qualitative case study approach, this study analyzes the characteristics of content and the number of viewers over the past three months. The research results indicate significant variations in the number of viewers and content characteristics on each platform. TikTok takes center stage with over 10 million followers and videos reaching millions of viewers. Furthermore, although Facebook only has 596 thousand followers, the platform demonstrates stability in reaching millions of viewers with content focused on inspirational stories and issues related to public figures. Fluctuations in the number of viewers from month to month reflect changes in user trends and preferences. Pojoksatu.id can adapt its content to changing trends, build a strong presence, and reach a broad audience by understanding the characteristics of each social media platform.